2020
DOI: 10.17582/journal.aavs/2020/8.s1.47.54
|View full text |Cite
|
Sign up to set email alerts
|

Moringa Oleifera Leaves Extract Ameliorates Melamine-induced Testicular Toxicity in Rats

Abstract: Many factors such as cryptorchidism, testicular torsion, varicocele, hyperthyroidism, infection, physical exertion, hormonal imbalance, the impact of xenobiotics induce the formation of reactive oxygen species (ROS) in the testis (Aitken and Roman, 2008). ROS is one of the principal causes of alteration in glucose homeostasis in testis, especially in terms of lactate production and modulation of LDH activity (Rossi et al., 2016) and apoptosis of germ cell (Rao and Shaha, 2000).Moringa oleifera (MO), a drumstic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Administration of MOLE in obesity-induced groups improved these parameters to similar levels as the control and MOLE groups. Our findings agree with previous studies, which reported that the administration of MOLE ameliorates tramadol-induced (Abd et al, 2020) or melamine-induced (Mansour et al, 2020) testicular injuries by abolishing oxidative stress and improving the seminal parameters in male rats.…”
Section: Discussionsupporting
confidence: 93%
“…Administration of MOLE in obesity-induced groups improved these parameters to similar levels as the control and MOLE groups. Our findings agree with previous studies, which reported that the administration of MOLE ameliorates tramadol-induced (Abd et al, 2020) or melamine-induced (Mansour et al, 2020) testicular injuries by abolishing oxidative stress and improving the seminal parameters in male rats.…”
Section: Discussionsupporting
confidence: 93%
“…It acts as an aldehyde to form SeNPs and stabilize the nanostructure of the formed nanoparticles. Meanwhile, the glucosinolates have been oxidized to gluconic acid [47,[62][63][64]. The reduction of Selenium cation can be made by some organic compounds.…”
Section: Synthesis Of In-situ Selenium Nanoparticles By Using Heterocyclic Compounds 12a 12b 13a 13b (Het-senps)mentioning
confidence: 99%
“…The importance of selenium nanoparticles (SeNPs) comes from their low toxicity and bioavailability. Moreover, they are biocompatible and can interact with proteins [47,48]. SeNPs are known as potent anticancer agents at high dosages [49].…”
Section: Introductionmentioning
confidence: 99%
“…Selenium (Se) is an essential trace element that is crucial for many cellular functions by the incorporation of selenoproteins (Skalickova et al, 2017). The importance of Selenium nanoparticles (SeNPs) come from its low toxicity, bioavailability, its interaction with proteins and biocompatible when compared to organic and inorganic selenium (Mansour et al, 2020;Ramamurthy et al, 2013). The selenium nanoparticles are known for its potent anticancer activity at high dosage (Fernandes and Gandin, 2015).…”
Section: Introductionmentioning
confidence: 99%